Language Attitude and Choice by Minangkabau Community: A Sociolinguistic Study in Medan - Deliana, Deliana; Ganie, Rohani; Raswiy, Nilzamy (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2017)
The objective of the research is to observe language attitude and choice of Minangkabau community residing in Medan to find out whether the people in the community have a positive or negative attitude toward Minangkabau language, and whether their language choice shows a preference toward Bahasa Indonesia, Minangkabau language, or other languages. This research was conducted in two subdistricts covering four villages in Medan. The data of this research were 400 copies of questionnaire whichcontained the respondents’ answers to 11 questions on language attitude and 18 questions on language choice. The data obtained were analyzed using Likert Scale for language attitude and domain analysis for language choice. It was found that the result of the language attitude was positive but in the language choice, respondents tended to use Bahasa Indonesia in the family, friendship, place, and media domains.